Telling a child he is HIV positive - C. Pfaff (South African Family Practice)
Telling a child he is HIV positive can create a number of difficulties. An example is given of a consultation where an 8 year old HIV positive child accidentally learnt of his diagnosis, while his mother continually denied this result to her child. The doctor tried to pressurise the mother into telling the child the truth and reflects on whether this was the best course of action. The issue of whether HIV positive children should be told the truth is discussed in the light of contrasting ethical issues: the autonomy of the mother versus the autonomy of the child; the autonomy of the mother versus the doctor's duty to tell the truth; the beneficence versus the maleficence of knowing the result; and family and cultural issues. From the lessons learnt, some recommendations are made regarding how to handle such difficult situations.